Arch and keystone, David Sassoon Clocktower - Ghosh, Ayan (2023)
Detail of arch and keystone with panels of Minto tiles and dressings of Blashfield's terracotta from Stamford, Lincolnshire. The David Sassoon Clock Tower is built from Porbandar stone, which was used in many public buildings of Mumbai, including Chhatrapati Shivaji Maharaj Terminus, Knesset Eliyahoo Synagogue, Bombay High Court, and Crawford Market.